Enhancing Community-Based Digital Promotion for Suban Lesung Tourism through Instagram Content Optimization: Peningkatan Promosi Digital Berbasis Komunitas untuk Pariwisata Suban Lesung melalui Optimalisasi Konten Instagram - Tiara Eka Putri; Endina Putri Purwandari; Hendy Santosa (Dharmakayana, 2025)
This community service program aimed to enhance community-based digital promotion capabilities for tourism managers of Suban Lesung, located in Talang Ulu Subdistrict, Curup Timur, Rejang Lebong Regency. The program was conducted over three months and involved ten local tourism management community participants. Initial field observations and pre-test results revealed a low level of understanding regarding digital promotion strategies, particularly in using Instagram Business features. A participatory training approach based on the Community-Based Training (CBT) model was implemented to address this, covering content planning, Instagram Business management, and targeted advertising through Instagram Ads. The evaluation was done using pre-test and post-test instruments, as well as an analysis of the @subanlesung account's digital performance. The results indicated a significant improvement in participants' understanding and the account's engagement metrics: a 36.27% increase in followers, over 100,000 content impressions, and notable audience growth especially among productive-age female users in Curup and Bengkulu. After the training, participants began independently managing content scheduling and production, including creating culturally inspired promotional materials. This initiative demonstrates that a structured, community-based digital training program can foster sustainable tourism promotion practices and empower local communities. The model also presents a scalable framework for similar rural destinations facing digital literacy and online branding challenges.